2019
DOI: 10.1371/journal.pntd.0007580
|View full text |Cite
|
Sign up to set email alerts
|

Risk profiling of soil-transmitted helminth infection and estimated number of infected people in South Asia: A systematic review and Bayesian geostatistical Analysis

Abstract: Background In South Asia, hundreds of millions of people are infected with soil-transmitted helminths ( Ascaris lumbricoides , hookworm, and Trichuris trichiura ). However, high-resolution risk profiles and the estimated number of people infected have yet to be determined. In turn, such information will assist control programs to identify priority areas for allocation of scarce resource for the control of soil-transmitted helminth infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…HII, a measure of human direct influence on ecosystems (Sanderson, et al,2002), showed a positive relationship with O. viverrini infection risk. A similar association has been found on HII and A. lumbricoides infection in South Asia (Lai, et al,2019). People living in areas with a longer distance to the nearest open water bodies tended to have lower risk, consistent with the previous finding (Forrer, et al,2012).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…HII, a measure of human direct influence on ecosystems (Sanderson, et al,2002), showed a positive relationship with O. viverrini infection risk. A similar association has been found on HII and A. lumbricoides infection in South Asia (Lai, et al,2019). People living in areas with a longer distance to the nearest open water bodies tended to have lower risk, consistent with the previous finding (Forrer, et al,2012).…”
supporting
confidence: 89%
“…The coordinates of the survey locations were obtained from Google Maps (https://www.google.com/maps/). Considering that areas are much smaller of ADM2 or ADM3, compared to that of ADM1, we treated surveys aggregated in ADM2 or ADM3 as point-level georeferenced at division centroids referring to previous studies (Lai, et al,2019), while surveys aggregated over ADM1 as area-level, in order to avoid large uncertainty in the later geostatistical analysis.…”
Section: Search Strategy Selection Criteria and Data Extractionmentioning
confidence: 99%
“…First, we assembled a set of environmental, socioeconomic and physical covariates for the analysis including: proportion of open defecation in 2011 and 2015, elevation, enhanced vegetation index (EVI), normalized difference vegetation index (NDVI), rainfall, soil PH, soil moisture, composition of the soil, night light emission, land surface temperature for day and night and number of MDA rounds. These covariates were chosen because they are either associated with the prevalence of any of the STH parasites or serve as a proxy for other factors that are known to drive the prevalence of any of the STH parasites [ 15 ]. The complete list of covariates and their values in the binomial geostatistical model are provided in supplementary material S1 Table (baseline) and S2 Table (impact assessment).…”
Section: Geospatial Covariate Selection and Testing For Spatial Residmentioning
confidence: 99%
“…Significant worldwide reductions in prevalence of Ascaris (-25.5% since 1990) have been estimated, but these reductions have been modest for Trichuris (-11.6%) and even smaller for hookworm (-5.1%) [2]. In more recent estimates (2015), 258 million (or 1 in 5) individuals in India are estimated to be infected with STH, with 148 million Ascaris, 109 million hookworm and 41 million Trichuris infections, indicating a lower prevalence of Ascaris and Trichuris, but a higher prevalence of hookworm than previous reports [3]. Moderate-and heavy-intensity (MHI) hookworm infections are (dw3data@uw.edu) for researchers who meet the criteria for access to these data.…”
Section: Introductionmentioning
confidence: 79%